Real-world evaluation of physiotherapist-led exercise prehabilitation and rehabilitation during autologous stem cell transplantation in myeloma: a single-centre experience - Orla McCourt; Joanne Land; Neil Rabin; Kwee Yong; Abi Fisher; Jonathan Sive; Charalampia Kyriakou; Michael K Luong; Alasdair Longden (BMJ Open Quality)
Background There is emerging evidence for the role of exercise in optimising function, quality of life (QoL) and reducing hospital length-of-stay if commenced prior to undergoing autologous stem cell transplantation (ASCT). A local pilot study of a prehabilitation and rehabilitation intervention during ASCT for myeloma patients indicated promising results and was adapted to translate into local clinical care. The aim of this report is to describe an overview of a newly implemented physiotherapist-led exercise prehabilitation and rehabilitation service delivered as part of the myeloma ASCT pathway, and present real-world findings related to changes in function and QoL.Methods A service evaluation was conducted at a single-centre tertiary referral hospital for haematopoetic stem cell transplantation in the United Kingdom. A hybrid service using face-to-face clinical assessments and weekly remotely supervised group exercise, via an online video conferencing platform, in the phase between stem cell harvest and admission (prehabilitation), and from discharge to 100 days post-ASCT (rehabilitation). Functional (6 min walk and timed sit-to-stand tests) and patient-reported outcome measures (European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire (EORTC-C30) and EuroQol EQ5D-5L were assessed at preharvest, preadmission and in the post-ASCT evaluation (day 100) clinic.Results Patients (n=46) with a diagnosis of multiple myeloma referred for ASCT following induction chemotherapy were assessed. Baseline assessments showed high prevalence of impaired function and lower limb strength. Improvements were evident following prehabilitation prior to admission, which were maintained post-ASCT. Changes in 6 min walk test and timed sit-to-stand were significant and beyond thresholds of clinical importance. Improvements were also seen in the domains of QoL.Conclusions Implementation of physiotherapist-led assessments in the myeloma clinic and group exercise delivery under remote supervision are acceptable to patients undergoing ASCT and indicate benefit in improving function and QoL.